SOCIAL MEDIA STRATEGIES IN DIGITAL MARKETING INFLUENCING MODERN-DAY CONSUMERS - Dr. Manish Kumar Jaisal, Sonali Singh, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Modern consumers who use digital technologies for shopping and entertainment are known as digital consumers. They cannot evade the influence of social media. Unavoidably, modern consumers are exposed to advertisements that indirectly raise their awareness of a product or service. The objectives of the strategies employed by social media marketers are to raise awareness and clarify the necessity of their products/services. Primarily, social media marketers utilize big data, which consists of various consumers' online activities collected from multiple sources, including search engines, e-commerce websites, and other online activities. These data are collected by marketers and analysed by artificial intelligence, which suggests the most effective individualised advertising strategies for each consumer segment. In this paper, the author explains how social media strategies enable digital marketers to influence and retain modern consumers for extended periods. The authors collect primary data from various modern consumers via Google forms and secondary data from previously published research articles, theses, blogs, and websites.